PENGARUH SUMBER INFORMASI PADA KEPUTUSAN PEMBELIAN YANG DI MODERASI POSITIVE PRODUCT KNOWLEDGE (Value : Jurnal Manajemen dan Akuntansi, 2022)
AbstractThe ability of producers to understand the factors that encourage consumers to make purchases online is one of the basic things that must be learned in order to be able to face the intense competition in today's digital era. This study examines the effect of evidential, confirmational and experientia lonline influence on online buying decisions which are moderated by positive product knowledge. There were 132 samples which were collected by distributing questionnaires through Google Form. The analytical method applied is regression analysis to test the direct relationship and subgroup analysis to test moderation. The results of this study state that confirmational and experiential directly have a significant effect on online buying decisions. Positive product knowledge is stated to be able to moderate the relationship between confirmational and experiential on online buying decisions. Meanwhile, evidential online influence directly or moderated by positive product knowledge has no effect on online buying decisions.Keywords: Evidential, Confirmational, Experiental, Product Knowledge, Buying Decision. AbstrakKemampuan produsen dalam memahami faktor yang mendorong konsumen dalam melakukan pembelian secara online, menjadi salah satu hal dasar yang harus dipelajari guna dapat menghadapi ketatnya persaingan di era digital saat ini. Penelitian ini menguji tentang pengaruh evidential, confirmational dan experiential online influence pada online buying decision yang dimoderasi oleh positive product knowledge. Terdapat 132 sampel yang dikumpulkan dengan menyebarkan kuesioner melalui Google Form. Metode analisis yang diterapkan adalah analisis regresi untuk menguji hubungan langsung dan analisis sub group untuk menguji moderasi. Hasil dari penelitian ini menyatakan bahwa confirmational dan experiential secara langsung berpengaruh signifikan pada online buying decision. Positive product knowledge dinyatakan dapat memoderasi hubungan antara confirmational dan experiential pada online buying decision. Sedangkan, evidential online influence secara langsung maupun dimoderasi oleh positive product knowledge tidak berpengaruh pada online buying decision.Kata Kunci: Evidential, Confirmational, Experiential, Pemahaman Produk, Keputusan Pembelian.